Biophysical regulation of macrophages in health and disease. Issue 2 (12th March 2019) - Meli, Vijaykumar S.; Veerasubramanian, Praveen K.; Atcha, Hamza; Reitz, Zachary; Downing, Timothy L.; Liu, Wendy F.
Abstract: Macrophages perform critical functions for homeostasis and immune defense in tissues throughout the body. These innate immune cells are capable of recognizing and clearing dead cells and pathogens, and orchestrating inflammatory and healing processes that occur in response to injury. In addition, macrophages are involved in the progression of many inflammatory diseases including cardiovascular disease, fibrosis, and cancer. Although it has long been known that macrophages respond dynamically to biochemical signals in their microenvironment, the role of biophysical cues has only recently emerged. Furthermore, many diseases that involve macrophages are also characterized by changes to the tissue biophysical environment. This review will discuss current knowledge about the effects of biophysical cues including matrix stiffness, material topography, and applied mechanical forces, on macrophage behavior. We will also describe the role of molecules that are known to be important for mechanotransduction, including adhesion molecules, ion channels, as well as nuclear mediators such as transcription factors, scaffolding proteins, and epigenetic regulators. Together, this review will illustrate a developing role of biophysical cues in macrophage biology, and also speculate upon molecular targets that may potentially be exploited therapeutically to treat disease. Abstract : Review on the role of biophysical cues in regulating macrophage function, and potential molecular mediators of mechanotransduction.